The Regulatory Role of MicroRNAs on Phagocytes: A Potential Therapeutic Target for Chronic Diseases - Wang, Yongbo; Liu, Xingyu; Xia, Panpan; Li, Zhangwang; FuChen, Xinxi; Shen, Yunfeng; Yu, Peng; Zhang, Jing (Frontiers in Immunology, 2022)
Abstract An effective acute inflammatory response results in the elimination of infectious microorganisms, followed by a smooth transition to resolution and repair. During the inflammatory response, neutrophils play a crucial role in antimicrobial defense as the first cells to reach the site of infection damage. However, if the neutrophils that have performed the bactericidal effect are not removed in time, the inflammatory response will not be able to subside. Anti-inflammatory macrophages are the main scavengers of neutrophils and can promote inflammation towards resolution. MicroRNAs (miRNAs) have great potential as clinical targeted therapy and have attracted much attention in recent years. This paper summarizes the involvement of miRNAs in the process of chronic diseases such as atherosclerosis, rheumatoid arthritis and systemic lupus erythematosus by regulating lipid metabolism, cytokine secretion, inflammatory factor synthesis and tissue repair in two types of cells. This will provide a certain reference for miRNA-targeted treatment of chronic diseases.